The year without summer : 1816 and the volcano that darkened the world and changed history - Klingaman, William K. (St. Martin's Press, 2013)
1816 was a remarkable year, mostly for the fact that there was no summer. As a result of a volcanic eruption in Indonesia, weather patterns were disrupted worldwide for months, allowing for excessive rain, frost, and snowfall through much of the Northeastern U.S. and Europe in the summer of 1816. The Year Without Summer examines not only the climate change engendered by this event, but also its effects on politics, the economy, the arts, and social structures.